The relationship between the aspects of connectedness and sustainable consumption - Jansen, Petra; Hoja, Sabine; Rahe, Martina (Frontiers in Psychology, 2024)
Internal transformative qualities are essential contributing factors to sustainable behavior. Besides awareness, insight, purpose, and agency, connectedness is one of those inner qualities. In this study, we investigated the relationship between connectedness to oneself (self-love), towards the environment (connectedness to nature), towards other human beings (pro-socialness), and sustainable behavior towards clothes and food. One hundred thirty-nine mostly students participated. The results showed that self-love, connectedness to nature, and pro-socialness correlate. Sustainability behavior towards food was predicted by pro-socialness, the choice of diet, and environmental and ethical reasons for nutrition. Sustainable behavior towards clothes was predicted by connectedness to nature. This study hints that the factors of inner transformative qualities and the type of sustainable behavior must be investigated differently. It strengthens the multi-facet dimensions of sustainable behavior.